4-Amino-1, 8-naphthalimide–ferrocene conjugates as potential multi-targeted anticancer and fluorescent cellular imaging agents. Issue 12 (2nd November 2021) - Johnson, Alex D.; Buhagiar, Joseph A.; Magri, David C.
Abstract : Eight ferrocenyl 4-amino-1, 8-naphthalimide logic gates for acidity and oxidisability are repurposed as anti-proliferation and cellular imaging agents against MCF-7 and K562 cancer cell lines. Abstract : Herein we present eight ferrocenyl 4-amino-1, 8-naphthalimides. Designed as fluorescent logic gates for acidity and oxidisability, the molecules have been repurposed as anti-proliferation and cellular imaging agents. The compounds were studied in vitro against MCF-7 and K562 cancer cell lines by the MTT method. Compounds with protonable secondary amines tended to exhibit greater cytotoxicity than those with tertiary amines. Compounds with no measurable GI50 values within a 24 hour time window, as well as at shorter exposure times, may be suitable as fluorescent cellular imaging probes.